Leadership Spaces at Zul Qarnain (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Zul Qarnain is an inspiring leader who appeared in an era of history. His story was recited in the Qur'an in Surat al – Kahf (verses 83 – 98). He is most likely the persain king Afridon ibn– Jamsheed , who was named the king of the West and East. Three military conquest campaigns in the West , East and North , aimed at calling for the worship and unification of God , spreading virtue in society , renouncing injustice and aggression , and helping people to live in dignity.He succeeded in that his leadership is wise based on justice, firmness, courage, know-how, competence and good morals. In line with the principles of the Islamic leadership, which deals with these qualities and qualities.